Significantly Enhanced Molecular Stacking in Ternary Bulk Heterojunctions Enabled by an Appropriate Side Group on Donor Polymer - Huanxiang Jiang (Advanced Science, 2020)
Abstract Ternary strategy is a promising approach to broaden the photoresponse of polymer solar cells (PSCs) by adopting combinatory photoactive blends. However, it could lead to a more complicated situation in manipulating the bulk morphology. Achieving an ideal morphology that enhances the charge transport and light absorption simultaneously is an essential avenue to promote the device performance. Herein, two polymers with different lengths of side groups (P1 is based on phenyl side group and P2 is based on biphenyl side group) are adopted in the dual‐acceptor ternary systems to evaluate the relationship between conjugated side group and crystalline behavior in the ternary system. The P1 ternary system delivers a greatly improved power conversion efficiency (PCE) of 13.06%, which could be attributed to the intense and broad photoresponse and improved charge transport originating from the improved crystallinity. Inversely, the P2 ternary device only exhibits a poor PCE of 8.97%, where the decreased device performance could mainly be ascribed to the disturbed molecular stacking of the components originating from the overlong conjugated side group. The results demonstrate a conjugated side group could greatly determine the device performance by tuning the crystallinity of components in ternary systems.